KONTRIBUSI PENDIDIKAN EKONOMI INFORMAL DAN LITERASI KEUANGAN TERHADAP KEMANDIRIAN EKONOMI PEREMPUAN UMKM DIMODERASI DUKUNGAN KELUARGA - Andi Tenri Ampa; Andi Tonra Lipu; Andi Annisa Sulolipu; Ika Wisudawaty; Maghfirah Sari Azis (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the contribution of informal economic education and financial literacy to the economic independence of women MSMEs in Makassar City, and to examine the role of family support as a moderating variable. The study used a quantitative approach with a survey of 375 female MSMEs across sub-districts throughout Makassar City. Data were collected through questionnaires and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that informal economic education positively contributes to women's economic independence by improving entrepreneurial knowledge, managerial skills, and confidence in economic decision-making. Financial literacy has also been shown to strengthen economic independence through improved cash flow management, financial planning, and more rational financial decision-making. Furthermore, family support plays a role in strengthening the relationship between informal economic education and financial literacy and economic independence, making individual capacity and social support complementary factors in promoting women's economic empowerment. This research enriches the study of economic empowerment based on human resources and financial capabilities and provides practical applications for policies to develop women's MSME empowerment at the regional level.  Keywords: informal economic education, financial literacy, family support, economic independence, women's MSMEs